Experiences of people living with HIV who have participated in psychological interventions: Protocol for a qualitative meta-analysis - Cristian Ortega; Jaime Garcia-Iglesias; Felipe Concha; Francisca Mena; Alemka Tomicic (PLoS ONE, 2026)
Introduction Mental health problems among people living with HIV have been widely documented, including a high burden of common mental disorders. Despite the demonstrated effectiveness of various psychological interventions, there is limited understanding of how these interventions are experienced and evaluated by participants themselves. A key factor in ensuring successful implementation lies in how individuals interpret and emotionally respond to an intervention—specifically, whether they perceive it as meaningful, appropriate, and aligned with their expectations and needs. This qualitative meta-analysis aims to explore the subjective therapeutic experiences of people living with HIV who have participated in psychological interventions, with a particular focus on their acceptability and the perceived impact on psychological well-being. Methods and analysis A qualitative meta-analysis will be conducted following the descriptive-interpretive approach, which enables the identification and synthesis of meaning units from participants’ narratives. The review will include qualitative and mixed-methods studies, with a clearly distinguishable qualitative component, published between January 1, 2000 and February 23, 2026, focusing on the therapeutic experiences of people living with HIV who have received psychological interventions for common mental health problems. A comprehensive search will be performed in MEDLINE (via PubMed), MEDLINE (EBSCOhost), Scopus, Web of Science, APA PsycINFO and SciELO. Methodological quality will be assessed using the CASP tool, and confidence in the findings will be evaluated through GRADE-CERQual. The data analysis will follow the descriptive-interpretive meta-analysis approach. Data management and thematic analysis will be supported by Microsoft Excel, Rayyan and/or ATLAS.ti. Expected results This review is expected to identify key experiential themes that reflect how people living with HIV perceive and evaluate psychological interventions, including the aspects they find most helpful, challenging, or relevant. Findings will contribute to a better understanding of the acceptability of such interventions and offer practical insights for improving their design, delivery, and contextual adaptation. Dissemination The results of this review will be disseminated through publication in a peer-reviewed journal and presentations at scientific conferences related to mental health, HIV, and qualitative research. The findings are expected to inform the development of more acceptable and culturally sensitive psychological interventions for people living with HIV.